Analysis of As-Built Microstructures and Recrystallization Phenomena on Inconel 625 Alloy Obtained via Laser Powder Bed Fusion (L-PBF) - Thibaut De Terris; Olivier Castelnau; Zehoua Hadjem-Hamouche; Halim Haddadi; Vincent Michel; Patrice Peyre (Metals, 2021)
The microstructures induced by the laser-powder bed fusion (L-PBF) process have been widely investigated over the last decade, especially on austenitic stainless steels (AISI 316L) and nickel-based superalloys (Inconel 718, Inconel 625). However, the conditions required to initiate recrystallization of L-PBF samples at high temperatures require further investigation, especially regarding the physical origins of substructures (dislocation densities) induced by the L-PBF process. Indeed, the recrystallization widely depends on the specimen substructure, and in the case of the L-PBF process, the substructure is obtained during rapid solidification. In this paper, a comparison is presented between Inconel 625 specimens obtained with different laser-powder bed fusion (L-PBF) conditions. The effects of the energy density (VED) values on as-built and heat-under microstructures are also investigated. It is first shown that L-PBF specimens created with high-energy conditions recrystallize earlier due to a larger density of geometrically necessary dislocations. Moreover, it is shown that lower energy densities offers better tensile properties for as-built specimens. However, an appropriate heat treatment makes it possible to homogenize the tensile properties.